2nd KHIBC Cancer Research Conference Amman, Jordan 02 - 03 Oktober 2009 - Suhair Abbas, Ahmed (Pusat Pengajian Sains Kesihatan, 2009)
Multiple myeloma (MM) is an ancient disease since bones showing typical MM: lesions have been detected in archeological remnants. However, the mortality trends in Malaysia suggest progressive increases in the incidence of the disease - , during the past fifty years. Nevertheless, this must be interpreted with caution because · MM: may have been under-diagnosed. In addition, it has been well-established that MM is ' a disease of the elderly, as the incidence increases steadily with increasing age to a peak age-specific incidence among people older than 80 years, with a median age of 65 years. In addition, MM: has also been reported to be more of an urban disease, than it is a rural one. Over the past few years, a different trend of occurrence ofMM has been noticed at the Hospital University of Science of Malaysia, especially regarding age distribution and type of environment, being urban or rural. Materials and Methods: To study this remark systematically, records of all patients with multiple myeloma at the Hospital ofUniversiti Sains Malaysia (HUSM), from 2005 - 2009 were reviewed. The data was collected and analyzed for the disease distribution according to gender, age group and area of residence. Results: Of the forty patients diagnosed with MM during the study period, in this study 25 (62.5%) patients were at the age group of 40-60 years. The remaining 15 (37.5%) were more than 60 years of age. The median age was 56 years. The sex distribution showed that twenty five patients (62.5%) were males and 15 patients (37.5%) were females, with a male to female ratio of 1.6. The urban: rnral distribution was 1:3, with 10 patients from urban areas, and 30 patients from rurat ·areas. Hence, 75% of all the 40 cases collected came from_ rural areas. Conclusion: The data obtained show that the age distribution of MM in the study area is lowered compared to most published reports. In addition, there is a rural predominance of occurrence of the disease as compared to findings in previously reported studies. These differences in the pattern of disease distribution may be attributable to environmental and occupational factors, including the use of agricultural pesticides, or the presence of other un-determined pollutants. Moreover, the possibility of genetic predisposition cannot be excluded.